2018
DOI: 10.1016/j.neo.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Mutation Status and Follicular Fluid Exposure Alters NFκB Signaling and ISGylation in Human Fallopian Tube Epithelial Cells

Abstract: Germline BRCA1 or BRCA2 mutations (mtBRCA1 and mtBRCA2) increase risk for high-grade serous ovarian cancer (HGSOC), the most commonly diagnosed epithelial ovarian cancer histotype. Other identified risk factors for this cancer, which originates primarily in the distal fallopian tube epithelium (FTE), implicate ovulation, during which the FTE cells become transiently exposed to follicular fluid (FF). To test whether mtBRCA1 or mtBRCA2 nonmalignant FTE cells respond differently to periovulatory FF exposure than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…We found that the mechanism/s downstream of L1 that bring about the increase in ISG15 involve NF-κB signaling, since blocking this pathway by various methods eliminated the ability of L1 to induce ISG15. Increased NF-κB signaling and elevated ISG15 expression were recently observed also in BRCA1 mutants of fallopian tube epithelial cells [19] and in ovarian cancer cells [20]. In addition, cRel, a subunit of NF-κB, was shown to bind and activate the ISG15 gene promoter, supporting the involvement of NF-κB in regulating the transcription of the ISG15 gene [21].…”
Section: Discussionmentioning
confidence: 79%
“…We found that the mechanism/s downstream of L1 that bring about the increase in ISG15 involve NF-κB signaling, since blocking this pathway by various methods eliminated the ability of L1 to induce ISG15. Increased NF-κB signaling and elevated ISG15 expression were recently observed also in BRCA1 mutants of fallopian tube epithelial cells [19] and in ovarian cancer cells [20]. In addition, cRel, a subunit of NF-κB, was shown to bind and activate the ISG15 gene promoter, supporting the involvement of NF-κB in regulating the transcription of the ISG15 gene [21].…”
Section: Discussionmentioning
confidence: 79%
“…HERC5 expression is also regulated by the cytokine interleukin 1 β (IL-1β) and tumor necrosis factor α (TNFα) in distinct signal transduction pathways. Moreover, recent studies have shown that ISG15, UBE1L, UBE2L6 and HERC5 are tightly regulated by nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)-an immunological protein complex that is involved in controlling diverse cellular responses to viral infection including cytokine production, DNA transcriptional regulation and interferon activation [33].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies to evaluate the effects of ISG15 on tumor growth and immune response by manipulating the presences of different immune cell types, including NK cells, in animal models could provide valuable insight into the roles of ISG15 in the immune tumor microenvironment. Recently research findings showed that decreased BRCA1 expression resulted in increased ISG15 expression and protein ISGylation in human fallopian epithelial cells [47]. Follow up studies on the relationship between BRCA mutation status and ISG15 expression levels in ovarian cancer cells may help us to understand the underlying genetic components that drive ISG15 expression.…”
Section: Discussionmentioning
confidence: 99%